PENGARUH MODIFIKASI ALAT BANTU BOTOL MINERAL DAN DAYUNG TANGAN TERHADAP KETERAMPILAN RENANG - Rizki Anggara; Akor Sitepu; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2016)
This study aimed to determine the effect of modification tools mineral bottle and hand paddle towards freestyle skills of swimming in class X.1 SMA Al-Kawtsar. This research method was experimental research with the study design